Strategi Komunikasi Kampanye dalam Meningkatkan Kesadaran Masyarakat Mengenai Pentingnya Pengelolaan Arsip di Dinas Kearsipan Provinsi Sumatera Selatan - Deace Eksci Asista; Sonia Nurprameswari (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze the campaign communication strategy implemented by the Archives Agency of South Sumatra Province (Sumsel) in an effort to raise public awareness about the importance of archive management, and to identify the resulting obstacles and impacts. The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation studies. The results showed that the Archives Agency of South Sumatra used a mixed-media approach, integrating face-to- face media (archival training and exhibitions) and digital media (social media and websites). The main obstacles faced included the limited human resources for communication and internal digital infrastructure, as well as low public interest and external geographical challenges. Overall, this strategy proved to be effective in providing measurable positive impacts on increasing cognitive (knowledge), affective (attitude), and conative (behavior/active participation) awareness of the community and Regional Apparatus Organizations (OPD) regarding the importance of archiving discipline